Breakfast Composition in Junior High School Students - Sheila Devi; Aly Diana; Setiawan Setiawan (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Adolescence is a time of rapid development that requires higher nutrient intake levels than in adulthood. However the habit of skipping breakfast has become very popular among adolescents. Skipping breakfast has negative effects such as difficulty in concentrating, growth impairment and decrease academic performance. Therefore, this study was conducted to identify the breakfast composisition of early adolescents in Jatinangor, Sumedang, Indonesia.Methods: A cross sectional study with non-probability sampling method, was conducted in a junior high school Jatinangor during the month of July 2013. Ninety six participants were included in this study. All the participants underwent an interview about the food intake for breakfast in seven days using eating pattern recall guidelines.Results: Overall, 37% of the respondents skipped breakfast. The mean of total calories among the adolescents who consumed breakfast was 286.06 (187.89) kcal. The amount of carbohydrate, fat and protein consumed was 29.23 (19.93) gram, 13.93 (13.29) gram and 8.78 (6.11) gram accordingly. The main reason for adolescent to skip breakfast was lack of time.Conclusions: Majority of the respondents have their breakfast before they go to school. Overall, the total calories comsumed is sufficient however the amount of protein consumed is low. [AMJ.2015;2(4):525–8] DOI: 10.15850/amj.v2n4.637